Association of contrast-induced nephropathy with risk of adverse clinical outcomes in patients with cardiac catheterization: From the CINC-J study. (15th January 2017) - Sato, Akira; Aonuma, Kazutaka; Watanabe, Makoto; Hirayama, Atsushi; Tamaki, Nagara; Tsutsui, Hiroyuki; Toyoaki, Murohara; Ogawa, Hisao; Akasaka, Takashi; Yoshimura, Michihiro; Takayama, Tadateru; Sakakibara, Mamoru; et al.
Abstract: Background: The association between the incidence of contrast-induced nephropathy (CIN) and subsequent clinical outcomes is unclear in Japan. We evaluated the association between CIN and cardiovascular and renal events after cardiac catheterization. Methods: The CINC-J multicenter prospective cohort study examined 853 patients undergoing cardiac catheterization from 27 hospitals. CIN was defined as increase in serum creatinine (SCr) ≥ 0.5 mg/dL or ≥ 25% from baseline between 48 and 72 h after exposure to contrast. Major adverse cardiovascular and cerebrovascular events (MACCE) included all-cause deaths, non-fatal myocardial infarction, acute decompensated heart failure (ADHF), and stroke. Renal events included newly-required hemodialysis and increase of SCr ≥ 2 × from baseline. Results: During follow-up periods (477 ± 214 days), CIN, MACCE, and renal events occurred in 44 (5.2%), 71 (8.3%), and 26 (3.0%) patients, respectively. Kaplan–Meier analysis showed that CIN yielded increasing risk for MACCE, ADHF, newly-required hemodialysis, and renal events. In multivariable Cox proportional hazards analysis, age (HR: 1.03; 95% CI, 1.00–1.07; P  = 0.0425), anemia (HR: 1.94; 95% CI, 1.08–3.61; P  = 0.0264), and diabetes mellitus (HR: 1.86; 95% CI, 1.10–3.21; P  = 0.0119) were independent predictors of MACCE, whereas CIN (HR: 7.78; 95% CI, 3.23–17.9; P  = 0.0005) and SCr (HR: 2.09; 95% CI, 1.56–2.73; P  = 0.0006) were independent predictors of renal events. Compared to subjects without both anemia and CIN as the reference, those with both were high risk for MACCE (HR: 3.97; 95% CI, 1.25–10.6; P  = 0.0218). Conclusion: CIN was a significant predictor of subsequent renal events after cardiac catheterization. CIN and anemia were associated with increased risk for worse long-term clinical outcome, especially when both were present.